1992
DOI: 10.1002/jlb.52.4.469
|View full text |Cite
|
Sign up to set email alerts
|

RAPID COMMUNICATION: A synthetic peptide homologous to retroviral envelope protein down-regulates TNF-α and IFN-γ mRNA expression

Abstract: We investigated the influence of CKS-17, a synthetic heptadecapeptide that corresponds to a highly conserved domain of the immunosuppressive retroviral envelope protein p15E, on staphylococcal enterotoxin B (SEB)-induced TNF-alpha gene expression in human peripheral blood mononuclear cells and highly purified human monocyte preparations, as well as the production of TNF-alpha protein, using human peripheral blood mononuclear cells. RNA hybridization studies show that CKS-17 inhibits SEB-induced TNF-alpha mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Cytokine mRNA levels were normalized on the basis of the level of human ,B-actin mRNA. As in prior reports using CKS-17 conjugated to BSA (18,22,25), MN21 consistently suppressed the stimulant-induced IL-2 and IFN-,y mRNA expression. This study further showed that MN21 inhibited the stimulant-induced expression of IL-12 p40 heavy chain mRNA.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Cytokine mRNA levels were normalized on the basis of the level of human ,B-actin mRNA. As in prior reports using CKS-17 conjugated to BSA (18,22,25), MN21 consistently suppressed the stimulant-induced IL-2 and IFN-,y mRNA expression. This study further showed that MN21 inhibited the stimulant-induced expression of IL-12 p40 heavy chain mRNA.…”
supporting
confidence: 83%
“…We previously demonstrated that CKS-17 acts directly on monocytes/macrophages (24)(25)(26) and that CKS-17-treated monocytes inhibit staphylococcal enterotoxin-induced IFN-y production by T lymphocytes (24). Both IL-10 and IL-12 are produced predominantly by macrophages (31,35,40,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of significance are observations by us and by others of the effect of this peptide on the immunoregulation of cytokines [17][18][19][20][21][22]. For example, CKS-17 strongly inhibited Th1 cytokines that were induced by a variety of stimulants such as staphylococcal enterotoxin, anti-CD3 plus anti-CD28, concanavalin A, and lipopolysaccharide.…”
Section: The Effects Of Cks-17 On Immunitymentioning
confidence: 85%
“…Furthermore, HERV envelope proteins like syncytin-2 have a highly conserved region called the immunosuppressive domain (ISD), which seems to be important for materno-fetal immune tolerance at the fetal sited cell layer of the placenta [17]. Additionally, the ISD peptide has immunosuppressive properties on human peripheral blood mononuclear cells and, for example, in mouse models of skin or peritoneal inflammation [18-20]. A diminished expression of syncytins is related to preeclampsia [21].…”
Section: Introductionmentioning
confidence: 99%